Material Approaches to Stretchable Strain Sensors. Issue 6 (13th January 2015) - Park, Jaeyoon; You, Insang; Shin, Sangbaie; Jeong, Unyong
Abstract: With the recent progress made in wearable electronics, devices now require high flexibility and stretchability up to large strain levels (typically larger than 30 % strain). Wearable strain sensors or deformable strain sensors have been gaining increasing research interest because of the rapid development of electronic skins and robotics and because of their biomedical applications. Conventional brittle strain sensors made of metals and piezoresistors are not applicable for such stretchable sensors. This Review summarizes recent advances in stretchable sensors and focuses on material aspects for high stretchability and sensitivity. It begins with a brief introduction to the Wheatstone bridge circuit of conventional resistive strain sensors. Then, studies on the manipulation of materials are reviewed, including waved structural approaches for making metals and semiconductors stretchable, the use of liquid metals, and conductive filler/elastomer composites by using percolation among the fillers. For capacitive strain sensors, the constant conductivity of the electrode is a key factor in obtaining reliable sensors. Possible approaches to developing capacitive strain sensors are presented. This Review concludes with a discussion on the major challenges and perspectives related to stretchable strain sensors. Abstract : Stretching the limits: Recent advances in stretchable strain sensors are reviewed in the material aspects of resistive and capacitive sensors, and issues to be solved for practical uses are also presented.